Effects of Tinospora crispa on production performances and nutrient utilizability in hybrid chickens: https://10.69692/SUJMRD06031630 - Keohavong , Bounmy; Maliya, Somphone (Souphanouvong University Journal Multidisciplinary Research and Development, 2021)
Abstract This study was designed to evaluate the effect of Tinospora Crispa (TC) on growth performance, carcass characteristics, meat quality and nutrient utilizability of hybrid chickens. Ten chicks were randomly distributed into each replicate pen (4 pens/treatment) at 30 day of age. Four treatment were randomly selected. TC at the level of 0.25%, 0.50% and 0.75% were supplemented with commercial diet as T1, T2 and T3, respectively. Control (T4) was fed commercial diet 100%. This study was carried out for total of 90 day. The result shown that final bodyweight of chicken from 45 day of age affected by TC (p<0.001). in contrast, bodyweight of chicken under day of age and overall feed intake did not affected (p>0.05), and overall bodyweight gain decreasing by increasing TC levels (p = 0.001). However, this study was shown that mortality, characteristics of external organs and feed per gain not differ (p>0.05). internal organs, raw meat and cooked meat sensory were differ (p<0.05). Consumers accepted the smell of raw meat and color of cooked meat of T1, T2 and T3 much better than T4 (p<0.001). In conclusion, this study shown that TC does not affected growth performance and external organs, but it is good improving in internal organ, meat quality and nutrient utilizability of hybrid chicken. Further study with varied levels and other related factors are needs to concern for finding more accurate results.